Pharmacotherapy patterns in patients with chronic idiopathic constipation beginning treatment with linaclotide or lubiprostone in the United States - Arpita Nag; Rebecca Bornheimer; Gerry Oster (BioExcel Publishing Ltd, 2020)
Background: Chronic idiopathic constipation (CIC) is a common gastrointestinal disorder in community settings. Limited information exists on its treatment with the prosecretory agents linaclotide and lubiprostone. This retrospective cohort study investigated real-world pharmacotherapy patterns of linaclotide and lubiprostone. Methods: Patients (≥18 years) with CIC who received linaclotide or lubiprostone between January 2013 and December 2015 were identified in a United States health insurance claims database. Follow-up was from the date of the earliest claim for either drug to the end of continuous enrolment or switch to the alternative agent. Patterns of pharmacotherapy, evidence of irritable bowel syndrome (IBS), and concomitant use of selective serotonin reuptake inhibitors were examined using the International Classification of Diseases, Ninth or Tenth Revision, Clinical Modification codes and National Drug Codes. Results: In total, 43,164 and 17,743 patients with CIC received linaclotide and lubiprostone, respectively (~80% women, mean age ~47 years). Approximately 40% of subjects (linaclotide: 40.1%; lubiprostone: 37.6%) had evidence of IBS. Over a mean follow-up of 17 months, mean (standard deviation) treatment duration in patients without IBS was 6.6 (7.9) months for linaclotide and 4.5 (6.5) months for lubiprostone. Treatment episodes >180 days were more common with linaclotide (36.1%) than with lubiprostone (23.2%). At 12 months, Kaplan-Meier estimates of switching from lubiprostone to linaclotide and from linaclotide to lubiprostone were 13.4 and 5.6%, respectively. The number of patients receiving serotonin reuptake inhibitors was unchanged with treatment (~22%). Conclusions: Most patients with CIC receive linaclotide or lubiprostone for <6 months; few remain on therapy for >1 year. Additional research is warranted to understand the potential reason(s) for early discontinuation.